Influence of critical parameters on nanoparticles-surfactant stabilized CO2 foam stability at sub-critical and supercritical conditions - Yekeen, Nurudeen; Kun, Tan Xin; Al-Yaseri, Ahmed; Sagala, Farad; Idris, Ahmad Kamal (Journal of Molecular Liquids, 2021)
The stability of CO2-foam stabilized via the synergy of nanoparticles and surfactants at downhole conditions is strongly affected by different process parameters such as temperature, CO2 state, nanoparticles concentration, as well as resident brine and oil in the reservoir. Influence of critical parameters on static and dynamic stability of nanoparticles-surfactant stabilized CO2-foam at sub-critical and super-critical conditions was investigated in this study. Firstly, extensive static and dynamic foam stability experiments were conducted at 80 °C and presence of 30 vol% hexadecane oil using formulation turbiscan, to screen different surfactants and nanoparticles. The best performing nanoparticles and surfactant were then selected at the screening stage for further foam stability tests to compare the performance of CO2 foam at sub-critical and super-critical conditions. The foam stabilized by SiO2 and sodium dodecyl sulfate (SDS) demonstrated consistent static and dynamic stability, with least spreading coefficient (-5.28 mN/m) and favourable Lamellae number (0.71). Increasing nanoparticles concentration increased the stability of sub-critical CO2 foam whereas an optimum nanoparticles concentration for maximum stability of the supercritical CO2 foam was obtained as 0.5 wt% SiO2. The static stability of sub-critical and supercritical CO2 foam increased with increased sodium chloride (NaCl) concentrations until 2 wt%. However, the super-critical CO2 foam demonstrated increasing pressure drop and lowest reduction in mobility with increasing NaCl concentration until 10 wt%. Highly durable foams were generated when oil with high viscosity, high density and high molecular weight oil was added into the foaming dispersions. Mechanistic investigation of foam stabilization revealed that thickness of pseudo-emulsion films, as well as particles adsorption and orientation at gas–liquid and liquid–liquid interface, are key controlling parameters of foam static and dynamic stability in presence of oil, brine and at high temperature.
Keywords: CO2 foam; Nanoparticles; Surfactant; Super-critical; Salinity; Oil